Analysis of External Economic Stability of the Czech Rebulic - Kuncl, Martin (2008)
The purpose of this paper is to analyse external economic stability of the Czech Republic. The external economic stability is defined and basic theory related to especially intertemporal approach to external balances is reviewed. Special consideration is given to the transition character of the economy. The descriptive as well as econometric analysis (VAR and cointegration models) find that the Czech Republic is not dangerously imbalanced. A potential threat is found to be reresented by government budget deficits due to the problem of twin deficits